Partial purification of a specific antigen of Treponema hyodysenteriae. - Baum, D H (1979)
A specific antigen of pathogenic Treponema hyodysenteriae was extracted from lyophilized cells of isolant B169 with hot phenol-water, isolated, and semipurified by starch block electrophoresis.